Developing psychomotor evaluation instrument of biochemistry practicum for university students of biology education - Etika Dyah Puspitasari; Mohamad Joko Susilo; Novi Febrianti (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
Practicum is one of the important aspects of the learning of biology. There is no psychomotor evaluation instrument that is valid and reliable. This study is aimed at developing a valid and reliable psychomotor evaluation instrument for biochemistry practicum. The study is developmental research using the 4-D model of ‘define, design, develop, and disseminate’. Instrument validation was carried out through construct validation. The findings show that the developed instrument is characterized by a high level of construct validity although the reliability measure is not very well-estimated. The instrument is constructed of four factors of perception, set, guided response, and mechanism developed into 80 statement items.